Pengaruh Teknik Analisis Transaksional untuk Meningkatkan Kemampuan Interaksi Sosial Siswa - Siti Hafiatul Wazira; Ishlakhatus Sa'idah (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2022)
Social interaction is a relationship between one or more individuals, where the behavior of one individual can influence, can change, and can improve other individuals. Social interaction will not occur if it does not meet the requirements, namely social contact and communication. Social contact, namely the existence of social relations between individuals with other individuals that are direct. Such as by touch, conversation, or face to face as a form of action and reaction. While communication is the process of delivering messages from one person to another which is carried out directly or with tools or media so that other people give certain actions or responses. The purpose of this study is to find out transactional analysis can improve students' social interaction skills and to determine the level of influence of transactional analysis techniques on students' social interaction skills at MAN 1 Pamekasan. The method used is quantitative research with an experimental approach. The subjects studied were 8 students. The data collection used is a questionnaire and interviews. The technique used is Wilcoxon non-parametric statistical data analysis. This study uses non-parametric research, because the subjects studied are only 8 students and included in the ordinal data. In the process of data analysis using the SPSS software application version 25.0. The results of this study indicate that transactional analysis techniques have an effect on increasing students' social interaction skills at MAN 1 Pamekasan. While the level of influence of transactional analysis techniques in improving the social interaction skills of class X IPA students at MAN 1 Pamekasan showed significant results, as evidenced by the results of the Wilcoxon test with an average increase of 4.50 and as evidenced by the Asympig.Sig value of 0.012, which was less than 0.0. 05 which means there is a significant increase in the value between the pre-test to the post-test. This is also reinforced by data from interviews conducted by researchers, students experience changes in behavior after being given treatment. So, it can be concluded that transactional analysis techniques are effective in increasing students' social interaction skills at MAN 1 Pamekasan.